2017
DOI: 10.1016/j.jclepro.2016.11.070
|View full text |Cite
|
Sign up to set email alerts
|

A study of the comparability of energy audit program evaluations

Abstract: There is a large untapped potential for improved energy efficiency in various sectors of the economy. Governmental industrial energy audit programs subsidizing the companies to conduct an energy audit are the most common policy in trying to overcome the energy efficiency gap. Evaluation studies have been carried out to gain knowledge about the success of a completed energy audit policy program. The evaluations were made in different ways and in addition focused on different performance indicators and used diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 18 publications
3
29
0
Order By: Relevance
“…In a comparison of the evaluations of five energy audit programmes, mainly targeting SMEs in Australia, Germany, Sweden and USA, Andersson et al [56] concluded that comparison is hampered due to inconsistency in categorisations of both energy efficiency measures and energy end-use data. The lack of guidelines for what performance indicators and free-rider effects to include in an evaluation and how to calculate those also complicates the comparison of programs.…”
Section: Energy Programmementioning
confidence: 99%
“…In a comparison of the evaluations of five energy audit programmes, mainly targeting SMEs in Australia, Germany, Sweden and USA, Andersson et al [56] concluded that comparison is hampered due to inconsistency in categorisations of both energy efficiency measures and energy end-use data. The lack of guidelines for what performance indicators and free-rider effects to include in an evaluation and how to calculate those also complicates the comparison of programs.…”
Section: Energy Programmementioning
confidence: 99%
“…Based on the results of the energy audit, a cluster of tasks is formed, the solution of which is aimed at energy saving and increasing the efficiency and reliability of the equipment. The electricity quality study is based on the specially developed technique for experimental investigation and analytical calculation of higher harmonics voltage and current in power supply systems [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Calculation Of Higher Harmonicsmentioning
confidence: 99%
“…Energy consumption by residential sector will rise by eight times by 2050, therefore it is essential that India develops strategies for efficient consumption of energy in residential sector to balance energy demand [5].…”
Section: Analyzing Energy Efficiency Factors Of Residential Towers Usmentioning
confidence: 99%
“…The highest rank among all subfactor is Energy Audits (BEA1). Because energy Audits are one of the efficient tools to overcome the energy efficiency gap in buildings, Energy audits can identify the shortcoming in current energy administration system and correct the irregularities [5]. The subfactor Building Automation System (EAW2) is the second top subfactor.…”
Section: Table-iii Weight For Main Factorsmentioning
confidence: 99%